Led-based Fourier spectroscopy of HD17O in the range of 10000-11300 cm−1. Analysis of the 3ν3 band. (January 2023) - Sinitsa, L.N.; Serdyukov, V.I.; Polovtseva, E.P.; Scherbakov, A.P.; Bykov, A.D.
Highlights: The absorption spectrum of the HD 17 О molecule have been studied in the range 10, 000-11, 300 cm −1 for the first time. New 698 transitions to the (003) upper vibrational state have been determined. New 139 energy levels were obtained. Abstract: We carried out measurements of the rotational-vibrational absorption spectrum of the HD 17 О molecule in the range of 10, 000–11, 300 cm −1 using the LED-based Fourier Transform spectroscopy technique. The spectrum was recorded using IFS-125M Fourier Transform spectrometer with a resolution of 0.02 cm −1, at a pressure of 29 mbar, and an optical path length of 2400 cm. The absorption rotational-vibrational spectrum was analyzed using a set of software programs capable of automatic searching and identifying spectral lines and fitting their parameters. As a result of the analysis, the centers and intensities of 698 spectral lines of the HD 17 О molecule in the 3ν3 band and the rotational energy levels of the vibrational state (003) were determined for the first time. These new experimental energy levels are compared with the results of "global" variational calculations. It was found that despite strong vibrational excitation the simple model of isolated vibrational state and Watson-type effective Hamiltonian describe rotational energy level pattern in the (003) vibrational state very satisfactory, excluding two levels which are strongly perturbed by a local resonance with the (051) state.